Análise da correlação de métodos de avaliação da pisada relacionada à ativação neuromuscular - Silva, José Lourenço Kutzke Morais da (2015)
The foot and ankle disorders are prevalent in the general population and one of the main reasons for primary care consultations. The prevalence of disorders of treading, assessing the severity of the biomechanical deformity, as well as evaluating the progress of treatment, are usually identified only by clinical and radiological analysis. However, in practice, the diagnosis made only with this approach, excluding the evaluation of the plantar muscle recruitment associated with dysfunctions seem to be sufficient to choose the most appropriate treatment, whereas the effective functioning of the foot, also depends on the correct functioning the musculoskeletal system. Thus, this study aimed to identify the most effective method of analysis of the medial longitudinal arch through baropodometry associated with electromyographic evaluation surface. We studied 43 healthy subjects of both sexes aged between 18 and 25, through baropodometry, being adopted four analysis methods of the medial longitudinal arch consisted of: Arch Index Plantar Chippaux-Smirak, Clarke angle, evaluation Cavanagh-Rodgers, and Viladot. After the evaluation, the above ratings were subjected to Pearson correlation Spermann and being compared with the recruitment of the anterior tibialis muscles, peroneus longus and gastrocnemius bilaterally. These values were determined by Surface electromyographic analysis (rms) in microvolts unit. It was found that the recruitment of the gastrocnemius muscles (medial and lateral) had low correlation with all methods. Have the peroneus longus muscles (0.308) and anterior tibialis (-0.308) showed only low correlation with Clarke analysis method. So with these figures presented it is clear that the Clarke method is unreliable for the analysis of the medial longitudinal arch, as well as the gastrocnemius muscles are not very active in the formation of this. Already Chippaux- Smirak and Viladot classification are more suitable for evaluation of ALM, the first of which stands out from the second, as the values for the anterior tibialis (53.9 ± 9.6) and peroneus longus (48, 5 ± 4.9) were more similar when evaluated the normal parameters for the classification of the medial longitudinal arch. Therefore it was found that the Chippaux-Smirak method was the most effective classification to be adopted computed baropodometric analysis for classification of ALM.